Obstacles to Scientific Research in the Faculties of Education at Shaqra University in the Kingdom of Saudi Arabia - Soltan Nacer Saoud ARIFI (Social Sciences Journal, 1970)
The study aims to identify the obstacles of the scientific research in faculties of education at theUniversity of Shaqra in Saudi Arabia from the viewpoint of the faculty members. The study follows thedescriptive approach. The study sample consists of 218 faculty members. To achieve this goal, theresearcher develops a questionnaire consisting of 39 paragraphs which are distributed on five areas:obstacles concerning the conditions of university work, obstacles related to the university administration,obstacles related to devices and facilities needed for scientific research, the obstacles related to the materialand moral matters, and constraints related to the professional growth related to scientific research. Theresults show that the estimates of faculty members of the level of scientific research barriers were high in allareas. The results show the absence of statistically significant differences in the estimates of the facultymembers at the level of impediments to scientific research faculties of education at the University of Shaqraattributed to the variables of academic rank and experience. In light of the results, the study recommendthat there is a nessecity to present necessary funds for faculty members to do research in the various fieldsand the best researches should take awards annually. That can be done through the establishment of jointfunds to support scientific research and spending in it. And to provide research information rules asadditional university and office services, and a broad base of information in the academic department to beused by teachers and graduate students as well.